Complete denture hygiene solutions: antibiofilm activity and effects on physical and mechanical properties of acrylic resin (Journal of Applied Oral Science, 2021)
Appropriated denture hygiene is a predictive factor for longevity of rehabilitation treatment and maintenance of the oral mucosal health. Although, disinfectant solutions are commonly used as denture cleansers, the impact of these solutions on acrylic resin-based dentures remain unclear. Objective: To evaluate, in vitro, the antibiofilm activity of complete denture hygiene solutions and their effects on physical and mechanical properties of acrylic resin. Methodology: For antibiofilm activity measurement acrylic resin specimens were contaminated with Candida albicans, Candida glabrata and Streptococcus mutans. After biofilm growth, the specimens were assigned to the hygiene solutions: Distilled water (Control); 0.2% Sodium hypochlorite (SH); Efferdent Power Clean Crystals (EPC) and 6.25% Ricinus communis (RC). The viability of microorganisms was evaluated by agar plate counts. In parallel, physical, and mechanical properties of the acrylic resin were evaluated after simulating a 5-year period of daily immersion in the previously mentioned solutions. The changes in surface roughness, color, microhardness, flexural strength, impact strength, sorption and solubility were evaluated. Data were compared by ANOVA followed by the Tukey test or Kruskal-Wallis followed by the Dunn test depending on the distribution (α=0.05). Results: Regarding antibiofilm action, SH eliminated all microorganisms while EPC and RC exhibited moderate action against S. mutans (p=0.001) and C. glabrata (p<0.001), respectively. Relative to effects on the physical and mechanical properties of the acrylic resin, RC led to higher values of color change (p=0.030), hardness (p<0.001), surface roughness (p=0.006) and flexural strength (p<0.001). Moreover, RC induced the highest values of changes in solubility (p<0.001). EPC promoted greater changes in surface morphology, whereas immersion in SH retained the initial appearance of the acrylic resin surface. All hygiene solutions reduced the impact strength (p<0.05). Conclusion: SH presented the most effective antibiofilm activity. In addition, changes on properties were observed after immersion in RC, which were considered within acceptable limits.